Manual acupuncture enhanced therapeutic efficacy in vascular dementia rat model: systematic review and network meta-analysis - Yuanyu Song; Yinghua Chen; Junfeng Li; Wei Sun; Fangfang Jin (Systematic Reviews)
Abstract Objective This study aimed to systematically evaluate the efficacy of electroacupuncture and manual acupuncture for treating vascular dementia and to determine the optimal acupuncture point combination scheme for efficacy. Methods The PubMed, Embase, Web of Science, Cochrane, CNKI, VIP, and Wanfang electronic databases were searched up to July 2024 to identify relevant randomized controlled trials. RevMan 5.4 software and Addis software were used to assess the risk of bias for each study, determine subgroup classifications, and conduct meta-analyses. Results A total of 29 RCTs involving 659 animals were ultimately included. The meta-analysis results revealed that acupuncture treatment had a significant effect compared with the vascular dementia model group [mean difference (MD) = − 21.68, 95% confidence interval (CI) (− 25.77, − 17.59), P < 0.00001]. Manual acupuncture demonstrated better efficacy than electroacupuncture did [MD = − 0.42, 95% CI (− 12.72, 12.27)]. Among the different acupuncture point combinations, the Baihui (GV20) + Dazhui (GV14) combination yielded the best efficacy [MD = − 23.03, 95% CI (− 30.02, − 16.04), P < 0.00001]. Compared with other acupuncture protocols, the experiment conducted by Caiyu Peng et al. exhibited superior efficacy [MD = − 24.96, 95% CI (− 92.68, − 40.76)]. Conclusion Acupuncture significantly improves cognitive function in rats with vascular dementia. Manual acupuncture is more effective than electroacupuncture. Among the different acupuncture point combinations, manual acupuncture at GV20 and GV14 yields the best results. Compared with other acupuncture protocols, the best efficacy was observed when the two-vessel occlusion (2VO) model was used in 230 ± 10 g SD rats; when the Mingmen (GV4), Dazhui (GV14), Fengfu (GV16), Baihui (GV20), Shenting (GV24), Shuigou (GV26), Neiguan (PC6), Dalin (PC7), and Laogong (PC8) acupoints were selected; and when manual acupuncture with reinforcing and reducing methods was used for 30 min per day for 14 days. Systematic review registration PROSPERO CRD42024551402